Beyond Sheol : rethinking the conceptual background of the poetic imagery in Psalm 23 and its possible parallels in Canaanite thanatological mythology - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2013)
Dissertation (MA (Semitic Languages))--University of Pretoria, 2006.